Impact of Terrorism on Agricultural Business in Borno State, Nigeria - Jelilov, Gylych; Ayinde, Ramat; Tetik, Selman; Bilal , Bilal; Olali, Natalia (Applied Studies in Agribusiness and Commerce, 2018)
This study examines the impact of terrorism on agribusiness in Borno state. Terrorist activities in Borno state dates back to 2009 where a group of Islamic extremists popularly known as Boko Haram (meaning western education is a sin) became violent in their activities. The group operates significantly in north-eastern Nigeria where Borno state is located and since 2009. The presence of the group has led to collapse of socio-economic activities in Borno state among other states. Millions of people have been displaced fromtheir homes and forced to live in camps in neighbouring states. As a result, this study examines the impact of insurgency related activities on agribusiness in BornoState. Agricbusiness in Borno state can be measured using four different parameters, amount of area cultivated, annual crop production, rearing of livestock and fish farming. These are the major agricultural business residents of Borno state are engaged in. However due to unavailability of data, rearing of livestock and fish farming are dropped, thus focusing on area cultivated and annual crop production. As a result of these two variables, two models are developed. The first model measures the relationship between amounts of crop produced with insurgency related killings, while the second model measuresthe relationship between total areasof farmland cultivated with fatalities resulting from terrorist activity. This study employs Ordinary Least Squares methodology and finds that both relationshipsreveal negative results thus indicating statistically significant negative impact of terrorism on agribusiness in Borno State.JEL Classification: Q10, Q18, Q12